2013
DOI: 10.1111/1440-1681.12102
|View full text |Cite
|
Sign up to set email alerts
|

A high‐fat diet and multiple administration of carbon tetrachloride induces liver injury and pathological features associated with non‐alcoholic steatohepatitis in mice

Abstract: The aim of the present study was to establish a progressive steatohepatitis mouse model because few reported animal models of non-alcoholic steatohepatitis (NASH) show the progression from fatty liver to steatohepatitis. C57BL/6N mice were fed a high-fat diet (HFD) to develop obesity and were either administered carbon tetrachloride (CCl4 ) eight times (0.05 mL/kg, s.c., once, followed by 0.1 mL/kg, s.c., seven times) or not. Serum parameters and hepatic histopathology were examined. In a separate experiment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 26 publications
6
56
0
Order By: Relevance
“…To avoid confounding effects of the absence of WDR13 per se on metabolism and the toxic effects of CCl 4 , the present study was conducted at the age of 8-10 weeks old animals when there is no onset of hyperinsulinemia and obesity. Fatty liver condition in mice has been reported upon treatment with CCl 4 along with high fat diet [42] via upregulation of PPARγ in the liver [43]. In this study we observed fatty liver phenotype in Wdr13 -/0 mice on CCl 4 treatment alone, owing to upregulation of PPAR pathway.…”
Section: Discussionsupporting
confidence: 63%
“…To avoid confounding effects of the absence of WDR13 per se on metabolism and the toxic effects of CCl 4 , the present study was conducted at the age of 8-10 weeks old animals when there is no onset of hyperinsulinemia and obesity. Fatty liver condition in mice has been reported upon treatment with CCl 4 along with high fat diet [42] via upregulation of PPARγ in the liver [43]. In this study we observed fatty liver phenotype in Wdr13 -/0 mice on CCl 4 treatment alone, owing to upregulation of PPAR pathway.…”
Section: Discussionsupporting
confidence: 63%
“…Only two experimental studies of native FGF21 or FGF21 analogues had implicated FGF21 in the treatment of MCD diet-induced NASH (Fisher et al, 2014;Ju et al, 2016). The MCD diet-fed mouse model has a number of disadvantages, including decreased bodyweight, serum triglycerides and glucose levels (Kubota et al, 2013). By using CD-HFD to induce a type of NASH associated with obesity and a human NASH-like pathology, we could focus on the effects of long-acting FGF21 on weight loss, as PsTag600-FGF21 treatment potently induced weight loss in DIO mice (Yin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of inflammation and fibrosis observed by Lee et al after feeding C57BL/6J mice a purely high‐fat diet for 10 weeks was remarkable given that mice are relatively resistant to the development of NASH with fibrosis. Moreover, it has been widely reported that even with prolonged high‐fat feeding, C57BL/6J mice develop scant or no hepatic fibrosis . As such, with the goal of identifying PAI‐1 antagonism as an antifibrotic therapy in NASH, we employed two distinct dietary models of murine NASH with fibrosis.…”
Section: Discussionmentioning
confidence: 99%